2003
DOI: 10.1076/opge.24.4.233.17230
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiology and ocular blood flow in a family with dominant optic nerve atrophy and a mutation in the OPA1 gene

Abstract: Patients with a mutation in the OPA1 gene have a very variable phenotype. MVEP and blood flow measurements are two new objective methods for an easier detection of this specific genetic optic nerve atrophy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 13 publications
3
20
1
Order By: Relevance
“…103 The applications and details of the mfVEP are outside the scope of this review and readers can refer to a review by Hood et al 100 Gränse et al used mfERG to demonstrate the macular function is normal in patients with dominant optic nerve atrophy due to mutation of OPA1 gene, whereas the mfVEP is abnormal. 76 Chen et al has also reported the use of mfERG and mfVEP in evaluating a patient with papillorenal syndrome and has confirmed that the visual field defects were due to retinal ganglion cell and optic nerve abnormalities rather than outer retinal dysfunction. 39 Studies on the use of mfVEP in glaucoma also appear to be promising as the mfVEP defects can reflect the changes in perimetry including glaucomatous visual field changes.…”
Section: Other Multifocal Techniquesmentioning
confidence: 98%
“…103 The applications and details of the mfVEP are outside the scope of this review and readers can refer to a review by Hood et al 100 Gränse et al used mfERG to demonstrate the macular function is normal in patients with dominant optic nerve atrophy due to mutation of OPA1 gene, whereas the mfVEP is abnormal. 76 Chen et al has also reported the use of mfERG and mfVEP in evaluating a patient with papillorenal syndrome and has confirmed that the visual field defects were due to retinal ganglion cell and optic nerve abnormalities rather than outer retinal dysfunction. 39 Studies on the use of mfVEP in glaucoma also appear to be promising as the mfVEP defects can reflect the changes in perimetry including glaucomatous visual field changes.…”
Section: Other Multifocal Techniquesmentioning
confidence: 98%
“…9,31 In addition, the electroretinograms in patients with ADOA are, in general, normal. 1,[41][42][43] Thus, the photoreceptor layer is most likely not affected in this disease. The overall sensory retinal thickness at the fovea was normal in patients with ADOA probably because the RNFL and ganglion cell layer are essentially absent in this area.…”
Section: Discussionmentioning
confidence: 99%
“…The amplitudes in a defined central region of the cortical response, where we usually obtain the best results ( Fig. 1) (Gra¨nse et al 2003), were measured and compared with those in 10 normal controls ( (Berson 1993). Electrophysiological findings in RP patients were reported as early as 1951 (Bjo¨rk & Karpe 1951), demonstrating that the electroretinograms were often extinguished.…”
Section: Multifocal Vepmentioning
confidence: 99%